PENGARUH EKSTRAK DAUN SUREN DAN DAUN MAHONI TERHADAP MORTALITAS DAN AKTIVITAS MAKAN ULAT DAUN (PLUTELLA XYLOSTELLA) PADA TANAMAN KUBIS - NURUL H, NINA Nurul (LenteraBio: Berkala Ilmiah Biologi, 2013)
Plutella xylostella is one of pests which can cause damage of cabbage plants. One of the ways in controlling this pest is using biopesticides, i.e. mahogany and surian leaf extracts. This research aimed to identify the effect of extract leaves of suren, mahogany and suren+mahogany  to mortality and eating activity of Plutella xylostella on cabbage plants. The research used two direction  of ANAVA i.e. the type and extract concentration. The extracts used were from suren, mahogany and suren+mahogany leaves, with concentration 6% suren extract, 8% suren extract, 10% suren extract, 6% mahogany extract, 8% mahogany extract, 10%  mahogany extract, 6% suren+mahagony extract, 8% suren+mahogany extract, 10%  suren+mahogany extract. This research was conducted in 3 replications  using 10 second instar larvae of Plutella xylostella for each treatment. Research parameters observed were mortality and eating activity of Plutella xylostella. Data are analyzed using Varians Analyze. The results of the research showed that the present of mahogany and suren leaf extracts influence the mortality and eating activity of Plutella xylostella. The treatment of 10% suren extract showed a higher influence than other treatments are cause mortality 85% and eating activity 57%.